2018
DOI: 10.1111/imj.13936
|View full text |Cite
|
Sign up to set email alerts
|

Media reporting of health interventions in New Zealand: a retrospective analysis

Abstract: New Zealand news articles covering medical treatments and interventions are largely consistent with available evidence but are incomplete. Vital information is being consistently missed, especially around the potential harms and costs of medical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(43 citation statements)
references
References 20 publications
0
43
0
Order By: Relevance
“… 28 , 30 , 31 , 33 – 36 However, even more studies used tools that were to some extent, directly or indirectly, based on the criteria developed by Moynihan et al . 37 This includes the four studies that used the Media Doctor Australia tool 12 , 13 , 38 , 39 and the 3 studies that used the Health News Review tool, 25 , 26 , 40 which was based on the Media Doctor Australia tool. 25 Two studies used two separate tools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 , 30 , 31 , 33 – 36 However, even more studies used tools that were to some extent, directly or indirectly, based on the criteria developed by Moynihan et al . 37 This includes the four studies that used the Media Doctor Australia tool 12 , 13 , 38 , 39 and the 3 studies that used the Health News Review tool, 25 , 26 , 40 which was based on the Media Doctor Australia tool. 25 Two studies used two separate tools.…”
Section: Resultsmentioning
confidence: 99%
“… 25 Two studies used two separate tools. 38 , 41 We did not identify any studies that used the Quality Index for health-related Media Reports 9 or the checklist for improving drug information in the general press. 10…”
Section: Resultsmentioning
confidence: 99%
“…Whether early detection and treatment of patients with CFRH reduces post-transplant renal dysfunction is currently unknown. 24 Hackman et al performed the first prospective study evaluating incidence and prevalence of diabetes postlung transplantation. Most reports estimate a prevalence of 25-40%, 18,19 and an incidence of 6-43% at 1 year 20,21 and 21-60% at 3-5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these data have been collected from multiple sources and retrospective studies without specific screening criteria for diabetes. 24 Hackman et al performed the first prospective study evaluating incidence and prevalence of diabetes postlung transplantation. They found that diabetes prevalence was 47%, 44% and 40% at 3, 12 and 24 months, respectively, and the incidence was 32%, 30% and 24% at 3, 12 and 24 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although Simon Cottle (1998, p. 25) says that Beck's assessment of the role of the media in risk society theory is underdeveloped, Beck's work is vital to understand the relationship between risk and media. Denney (2005), Brindle (1999), Robinson et al (2018) have made different theoretical assessments of the media's reporting of risks. For example, according to Denney (2005, p. 83), media sometimes reflects risks more valuable than they are, and Brindle (1999) states that the news value of risks are higher in case they actualise.…”
Section: Sonuçmentioning
confidence: 99%